Three new nematode species (Chromadorida: Selachinematidae) from the continental slope of New Zealand - Daniel Leduc; Zeng Qi Zhao (European Journal of Taxonomy)
Three new species of selachinematid nematodes, Choanolaimus serieporus sp. nov., C. sparsiporus sp. nov. and Gammanema lunatum sp. nov., are described from the continental slope of New Zealand. We also provide partial ribosomal DNA SSU and LSU D2–D3 sequences for Gammanema lunatum sp. nov. and another selachinematid species, Halichoanolaimus funestus Leduc, 2020. Until now, the genus Choanolaimus de Man, 1880 comprised a single species restricted to coastal dunes, beaches and estuarine environments of the North Sea, Northeast Atlantic and Northeast Pacific. To our knowledge, the present study provides the first record of the genus from the southern hemisphere and from the deep-sea environment (> 250 m depth). The two new species of Choanolaimus are characterised by two longitudinal dorsosublateral rows of pore complexes, which differ in arrangement between species thus providing a taxonomically informative character. The presence of pore complexes in Choanolaimus is consistent with previous findings, which show that within the Selachinematidae Cobb, 1915, pore complexes are only found in genera with a blind intestine. The two species of Gammanema Cobb, 1920 known so far from New Zealand share characters not found in any other species of the genus, i.e., loop-shaped amphids in males and the presence of cuticle spines, which indicates that these two species may have evolved from a common ancestor. The SSU and LSU D2–D3 consensus trees are largely congruent. Our molecular phylogenetic analyses confirm previous results, which support the monophyly of the family Selachinematidae but not of the subfamilies Selachinematinae and Choniolaiminae, with some genera placed in different clades despite sharing strong morphological similarities. We have found no support for the monophyly of the genus Halichoanolaimus de Man, 1886, which forms a well-supported clade with the genera Bendiella Leduc, 2013, Cobbionema Filipjev, 1922 and Demonema Cobb, 1894.